1993
DOI: 10.1172/jci116645
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acids regulate hepatic low density lipoprotein (LDL) transport by altering LDL receptor protein and mRNA levels.

Abstract: The concentration of LDL in plasma is strongly influenced by the amount and the type of lipid in the diet. Recent studies in the hamster have shown that dietary fatty acids differentially affect circulating LDL levels primarily by altering receptor-dependent LDL uptake in the liver. To investigate the mechanistic basis of this effect, rates of receptor-dependent LDL transport in the liver were correlated with LDL receptor protein and mRNA levels in hamsters fed safflower oil or coconut oil and varying amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
2
5

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 45 publications
3
49
2
5
Order By: Relevance
“…Liver LDL-r removes LDL-cholesterol from circulation, thereby maintaining cholesterol homeostasis (12). A high-SFA intake during the postnatal time period has been reported to lower the expression of hepatic LDL-r in several animal models (19,30,31,55) and in human studies (29). The LDL-r mRNA expression was significantly reduced in the female S/S and C/S offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver LDL-r removes LDL-cholesterol from circulation, thereby maintaining cholesterol homeostasis (12). A high-SFA intake during the postnatal time period has been reported to lower the expression of hepatic LDL-r in several animal models (19,30,31,55) and in human studies (29). The LDL-r mRNA expression was significantly reduced in the female S/S and C/S offspring.…”
Section: Discussionmentioning
confidence: 99%
“…SFA intake raises plasma LDL levels (54,60) and inhibits the expression of hepatic LDL-receptor (LDL-r) (29,31). Both in vitro and in vivo studies have shown that aortic endothelial function may be abnormal within a few hours of exposure to increased levels of LDL cholesterol (32,40).…”
mentioning
confidence: 99%
“…Hepatic ACAT activity and cholesteryl ester levels are sensitive to the fatty acid composition of dietary lipid, being higher in animals fed unsaturated fatty acids compared to those fed saturated fatty acids (29,30). We previously showed in the hamster that hepatic LDL receptor …”
Section: Resultsmentioning
confidence: 99%
“…In the hamster, polyunsaturated fatty acids upregulate hepatic LDL receptor expression and lower plasma LDL concentrations when compared to saturated fatty acids (29).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation